Relationship between Economic Growth and Environmental Degradation: Is there Evidence of an Environmental Kuznets Curve for Brazil? - Zambrano-Monserrate, Manuel A.; Valverde-Bajana, Ivanna; Aguilar-Bohorquez, Joseph; Mendoza-Jimenez, Maria Jose (International Journal of Energy Economics and Policy, 2016)
This study investigates the relationship between CO2 emissions, economic growth, energy use and electricity production by hydroelectric sources in Brazil. To verify the Environmental Kuznets Curve (EKC) hypothesis we use time-series data for the period 1971-2011. The Autoregressive Distributed Lag (ARDL) methodology was used to test for cointegration in the long run. Additionally, the VECM Granger causality test was applied to verify the predictive value of independent variables. Empirical results find that there is a quadratic long run relationship between CO2 emissions and economic growth, confirming the existence of an EKC for Brazil. Furthermore, energy use shows increasing effects on emissions, while electricity production by hydropower sources has an inverse relationship with environmental degradation. The short run model does not provide evidence for the EKC theory. The differences between the results in the long and short run models can be considered for establishing environmental policies. This suggests that special attention to both variables -energy use and the electricity production by hydroelectric sources- could be an effective way to mitigate CO2 emissions in Brazil. Keywords: Environmental Kuznets Curve, Energy, Hydroelectric Power, Brazil JEL Classifications: C32, O54, Q50, Q5